Perspectivas Teóricas, Como Basamentos Para Estudiar la Gestión Universitaria - Abello-Romero, J (Centro Universitario de Anapolis, 2023)
It is a great challenge to manage any organization successfully, and in Universities -our subject matter- the challenge is even bigger, considering these entities represent complexity par excellence. The aim of this work is to carry out a theoretical review of the Agency theory, Stewardship theory, and Stakeholder theory, which can help improve the praxis of management in universities. In order to achieve the outlined goal, documentary research was carried out, reviewing academic articles of the subject area that were published in indexed journals from the main databases (secondary sources of information). Generally speaking, it is inferred that in a "liquid" and "hyper-complex" organizational scenario, any approach to the phenomena associated with University Management must be carried out from the multidimensionality of these educational entities. Accordingly, this study provides background information that can serve as a basis for creative solutions to the problems of efficiency, effectiveness, and quality faced by universities. © 2021 by the authors.